Penentuan kadar vitamin c pada jeruk nipis (Citrus aurantiifolia) dan cabai rawit (Capsicum frutescens) - Ma'la, Zilvia Inayatul (Maliki Interdisciplinary Journal, 2024)
Vitamins are one of the important substances needed by humans. Vitamins can keep the body healthy and can help the metabolic process to run well. One type of vitamin is vitamin C or L-ascorbic acid. Vitamin C is an acidic compound with the empirical formula C6H8O6 molecular weight = 176.12 g/mol) which is also a sugar acid found in many fresh fruits and vegetables (Ariani & Muhsin, 2023). The research at this time aims to determine the levels of vitamin C in lime (Citrus aurantiifolia) and cayenne pepper (Capsicum frutescens) by iodometric titration by doing two repetitions on each sample. This iodometric titration method is a method that is widely used because it does not require large costs, is simple, and does not require complicated laboratory equipment. The results of this study were obtained vitamin C levels in lime (Citrus aurantiifolia) as much as 0.1736% and cayenne pepper (Capsicum frutescens) as much as 0.25%.